Mengungkap Peran Minat Beli: Mediasi antara Citra Merek dan Viral Marketing dalam Mendorong Keputusan Pembelian - Azis, Santika Abd; Suci, Rahayu Puji; Zulkifli, Zulkifli; Iswari, Hanif Rani (Image : Jurnal Riset Manajemen, 2023)
This research discusses the decline in purchasing decisions at Deliwafa Store Malang Branch in the last few months, as an indication of changes in consumer purchasing behavior which can have an impact on overall business performance. The focus of the research is the influence of brand image and viral marketing on purchasing interest, as well as the implications for purchasing decisions. The research method used is quantitative with explanatory research type, using smart partial least squares (PLS) for data analysis. The research results show that brand image does not have a positive and significant influence on purchasing decisions, while viral marketing and purchase interest have a positive and significant influence on purchasing decisions. This highlights the important role of viral marketing and purchase intention in influencing consumer purchasing decisions, and suggests that brand image may not be the only determining factor in the purchasing process.